Efficacy of Intense Pulse Light with Triple Combination Cream Versus Triple Combination Cream alone in the Treatment of Melasma - Anshul Verma; Sudha Agrawal (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Various studies explored the use of intense pulse light (IPL) therapy in treating melasma, but only a few randomized clinical trials have evaluated the combination of triple combination cream (TCC) with IPL so far.